New York Paper - Schedule Rating Coal Mines in Pennsylvania for Compensation Insurance Rates (with Discussion) - Rush N. Hosler (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1925)
This paper was prepared for the purpose of answering some of the many questions as to why, in the construction of Pennsylvania's Coal Mine Schedule Rating Plan, various factors were, or were not, taken into consideration. Much has been written about merit and schedule rating of industrial risks from an actuarial viewpoint, therefore this phase of the question is taken up only so far as may be necessary in presenting the practical application of the plan now in use. Companies writing fire insurance, about 30 years ago, were the first branch of insurance to use schedule rating; the values assigned their items were largely a matter of judgment. In 1913, the Industrial Commission of Wisconsin evolved the first schedule rating plan to be applied to industrial risks under compensation insurance. Pennsylvania, in 1916, with the inception of its Compensation Act, was the first state to apply the principles of schedule rating to coal mines. A definition of the term "schedule rating" submitted by the writer in a brief to the Safety Committee of the United States Coal Commission is as follows: Schedule rating, as applied to compensation insurance, is an instrument to measure the hazard of known causes of accidents to which employees are exposed in industry and thereby determine an insurance rate commensurate with said hazard. It was first applied to Coal Mining in 1916 in Pennsylvania.' In other words, for a mine operator to insure his employees for injury under the Workmen's Compensation Act, it is necessary that he pay a certain premium based on his payroll. If all mines were assessed the same premium, it would be unfair for the mine with low natural hazard, good safety conditions, and good accident experience to pay the same premium as a mine with bad conditions and experience, therefore schedule rating was introduced.2